Hybrid Modeling Approaches for Solving Multi-Scale Problems in Engineering - Chavez, Janelle Sophia; Mercado, Tristan Alexander (Etunas Sukses Sistem, 2023)
Multi-scale problems in engineering often require modeling approaches that effectively integrate phenomena occurring across different spatial and temporal scales. Hybrid modeling approaches provide a promising solution by combining the strengths of numerical and analytical methods from various scales to enhance both accuracy and computational efficiency. This article reviews a range of hybrid techniques for addressing multi-scale challenges, including the integration of micro- and macro-scale models, coupling discrete and continuum simulations, and the application of multilevel methods in engineering analysis. Case studies from diverse engineering disciplines are presented to illustrate the potential benefits and challenges of hybrid modeling approaches. Leveraging these methods aims to deliver more realistic engineering solutions while optimizing computational resources.